Perbandingan umkm yang memanfaatkan digitalisasi dan non digitalisasi di Lamongan pada era covid-19 - Kurnia, Arini Ayu; Wulandari , Dwi (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
Digital disruption and the Covid-19 pandemic are challenges for MSMEs who have not used digital to survive in two conditions simultaneously which have caused many changes in mindset in shopping. The conventional world that exists with its achievements seems to be eroded by changes in disruptive innovation. High sales degradation is felt by MSMEs that have not used digital, while MSMEs that have utilized digital are classified as experiencing low degradation. This study aims to emphasize MSME actors in Lamongan Regency to switch to digitalization by comparing the use of digital media used by MSME actors who have implemented and MSME actors who have not used digital media. The research method used is a qualitative method with a descriptive approach. The results of the study showed that out of 34 respondents who had used digital, there were 16 respondents who had used the application. It can be concluded that degradation is equally felt by non-digital MSMEs and MSMEs that have used digital, but MSMEs that have not used digital experience high degradation.